Simulation on gap bypass flow of the prismatic high temperature gas cooled reactor core - DONG Jianhua; WANG Jun; GUO Juanjuan; ZHANG Shuoting (He jishu, 2021)
BackgroundThe core of prismatic high temperature gas-cooled reactor (HTGR) is composed of fuel blocks based on layers and zones. Due to machining deviation and assembly, the gap size between blocks should be ensured. Part of the core coolant will be bypassed into these formed gaps, which can be abbreviated to gap bypass flow.PurposeThis study aims to analyze the impact of gap bypass flow on the thermal-hydraulic performance of the prismatic HTGR which is an important to the core structure and internal design.MethodsFirst of all, the commercial CFD (computational fluid dynamic) software ANSYS CFX was used to carry out the three-dimensional numerical simulation of the complex flow and heat transfer phenomena in MHTGR-350 (modular high-temperature gas reactor 350 MWt) active core. Then the detailed model of blocks, fuel holes, coolant channels and gaps were established to calculate the flow and temperature distribution in the region. Finally, the key parameters of these models were adopted for the sensitivity analysis.ResultsThe calculation results show that the flow rate into the long and narrow gap is mainly determined by the core structural arrangement and the gap size. When the gap size becomes larger, the bypass ratio will also be larger, the cooling efficiency will become worse, and the local fuel temperature will rise.ConclusionsThe gap size will change with the deformation of the core blocks during the operation life of the reactor, which will cause fluctuations in temperature distribution and outlet temperature. Furthermore, the larger the gap, the greater fluctuation range, which is detrimental to the safety and stability of the core operation.